Identifikasi Bahaya dan Penilaian Risiko Keselamatan dan Kesehatan Kerja: Studi Kasus: Pembangunan Gedung Rektorat Universitas Muhammadiyah Kendari - Artamil, Ld.; Wibowo, Dwiprayogo; Assiddieq, Moch. (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2023)
The high number of work accidents in construction projects shows that there is still a lack of understanding and application related to occupational safety and health (OSH), so that every party involved in project implementation needs to understand and apply OSH to minimize the occurrence of work accidents. This study aims to identify OSH in the construction project of the Rectorate building of Universitas Muhammadiyah Kendari (UMKendari) to provide educational office facilities as a center for management and academic services based on high technology. The research method is to identify potential hazards that cause work accidents and apply OHS standards using the Hazard Identification Risk Assessment and Determining Control (HIRADC) method. Specifically, this research identifies hazards, assesses risk levels, and provides risk control efforts in the construction of the Rectorate building. Based on this research, 4 stages of construction were obtained, namely preliminary work, structural work, architectural work, and mechanical, electrical, and plumbing (MEP) work. There are 112 potential hazards with 13 potential hazards are at low risk level, 36 potential hazards are moderate, 57 potential hazards are high, and 6 potential hazards are very high. We suggest for OHS implementation where potential risks and assessments are needed to reduce work accidents by administrative control, elimination, substitution, control techniques, and personal protective equipment (PPE).